A tough polyester heat-shrinkable film that is not prone to brittle fracture and its preparation method
By using toughening-crystal nucleation composite agent in the polyester heat shrink film, the problem of brittle fracture of the polyester heat shrink film is solved, and the effect of improving toughness and extending service life is achieved.
Patent Information
- Application Number
- CN202411816354.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Polyester heat shrink film is prone to brittle fracture during long-term use or storage, resulting in a decrease in toughness.
The toughening-crystal nucleation composite agent is used to improve the toughness and crystallization rate of the polyester heat shrink film by combining modified nanosilicon dioxide, modified nanohydrotalcite, ASA high glue powder and end carboxylic hyperbranched polyester.
It significantly improves the elongation and toughness of the polyester heat shrink film, extends its service life under different environmental conditions, and avoids the occurrence of brittle fracture.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a high-toughness polyester heat shrinkable film which is not prone to brittle fracture and a preparation method thereof, belonging to the technical field of polymer packaging materials. Background Art
[0002] Polyester heat shrinkable film is non-toxic and tasteless and has good mechanical, optical and printing properties. When used in the packaging field, it can be recycled together with the PET packaging body, which saves costs and meets environmental protection requirements. Therefore, the demand for polyester heat shrinkable film in the field of commodity packaging is growing, and the market prospect is very broad. When pure polyethylene terephthalate (PET) is used for heat shrinkable film, the shrinkage rate of the heat shrinkable film is very low, not exceeding 30%, which cannot meet the actual application requirements. Therefore, the pure PET resin must be chemically modified. The general principle followed by PET resin modification is: introducing flexible segments and asymmetric structures into the polyester molecular chain. Commonly used modified monomers include isophthalic acid, neopentyl glycol, cyclohexanediol, etc. In addition to modifying the chemical structure of polyester, the production process of polyester heat shrinkable film must also adopt a stretching process. Generally, uniaxial stretching or biaxial stretching processes are commonly used to improve the shrinkage rate of heat shrinkable film. At present, combined with the improvements in polyester molecular structure and stretching process, the shrinkage rate of polyester heat shrinkable film has basically met the needs of practical applications. However, during long-term storage or use, polyester heat shrinkable film is prone to a sharp drop in elongation at break due to the influence of temperature, humidity or other environmental factors. The macroscopic manifestation is that the toughness of the heat shrinkable film becomes poor and brittle fracture is prone to occur. This may be due to the slow crystallization inside the polyester resin induced by external environmental conditions or the accumulation of excessive stress during the stretching and cooling process induced by the external environment and concentrated release. Therefore, in order to solve the problem of brittle fracture during the use of polyester heat shrinkable film, it is necessary to conduct in-depth research and improvement on the molecular structure of polyester resin, the raw material formula of heat shrinkable film polyester resin and the stretching process, so as to improve the toughness of polyester heat shrinkable film as much as possible and avoid the occurrence of brittle fracture.
[0003] Chinese patent CN115491000A discloses a low-temperature high-toughness polyester shrink film for heat shrink labels and its preparation method and application. The raw material composition for preparing the low-temperature high-toughness polyester shrink film includes a polyester composition and an additive. The polyester composition, calculated by mass percentage, includes 40% to 99.9% of diol-modified polyethylene terephthalate, 0.1% to 30% of thermoplastic polyester resin, and 0% to 30% of dibasic acid-modified polyethylene terephthalate or polyethylene terephthalate; the mass of the additive is 500ppm to 1500ppm of the total mass of the polyester composition. The low-temperature high-toughness polyester shrink film obtained in the patent is prepared by a uniaxial stretching process. Its elongation at break in the stretching direction is not particularly high, not exceeding 300%, and the toughness is not particularly ideal. Moreover, the patent does not disclose whether the elongation at break of the polyester shrink film can be maintained in a relatively good state during long-term storage or use, and whether it is prone to brittle fracture.
[0004] Chinese patent CN105885024A discloses a flexible polyester heat shrinkable film and its production method, which mainly includes the following raw materials by weight: terephthalic acid: 100 parts; isophthalic acid: 0-15 parts; ethylene glycol: 50-80 parts; 1,4-cyclohexanedimethanol: 5-30 parts; polyester diol: 5-30 parts; polyether diol: 30-60 parts; ethylene glycol antimony: 0.1-0.5 parts; trimethyl phosphate: 0.05-1 parts. The flexible polyester heat shrinkable film obtained by the patent has a maximum transverse heat shrinkage rate of 86%, which can meet the use requirements in the packaging field, but the patent does not disclose the toughness of the flexible polyester heat shrinkable film and the change of toughness during the long-term use cycle.
[0005] From the above, we can see that the polyester heat shrinkable film still has the outstanding problem of poor toughness and easy brittle fracture during use. Therefore, the development of a strong and tough polyester heat shrinkable film that is not prone to brittle fracture has very important practical value and realistic significance. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a strong and tough polyester heat shrinkable film that is not prone to brittle fracture and a preparation method thereof, so as to achieve the following invention objectives: to prepare a polyester heat shrinkable film that is not prone to brittle fracture and has good toughness, high elongation at break and can be maintained for a long time.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] A strong and tough polyester heat shrinkable film that is not easy to be brittle and a preparation method thereof, wherein the raw material formula of the strong and tough polyester heat shrinkable film that is not easy to be brittle and is calculated by weight:
[0009] 40~100 parts of pure polyethylene terephthalate,
[0010] 15-50 parts of glycol-modified polyethylene terephthalate,
[0011] 4-15 parts of polybutylene terephthalate,
[0012] Toughening-crystallization nucleation compound 3~13 parts,
[0013] 1~3.5 parts of crystallization accelerator,
[0014] 0.5~2 parts of opening lubricant,
[0015] Filler 0~15 parts;
[0016] The pure polyethylene terephthalate has a glass transition temperature of 75-85° C., a melting temperature of 250-270° C., an intrinsic viscosity of 0.5-0.7 dl / g, and a number average molecular weight of 15000-20000 g / mol;
[0017] The diol-modified polyethylene terephthalate is polyethylene terephthalate co-modified with neopentyl glycol and diethylene glycol, wherein the molar percentage of neopentyl glycol is 25-35%, and the molar percentage of diethylene glycol is 5-15%;
[0018] The diol-modified polyethylene terephthalate has a glass transition temperature of 70-83° C., a melting temperature of 220-260° C., an intrinsic viscosity of 0.4-1.0 dl / g, and a number average molecular weight of 17000-21000 g / mol;
[0019] The polybutylene terephthalate has a glass transition temperature of 43-50° C., a melting temperature of 220-240° C., an intrinsic viscosity of 0.6-1.0 dl / g, and a number average molecular weight of 35000-40000 g / mol;
[0020] The crystallization accelerator is a mixture of trimesic acid amide and 1,2,3-propane tricarboxamide, and the mass ratio of the two is 1-10:13;
[0021] The opening lubricant is silicon dioxide with a particle size of 1 to 5 μm;
[0022] The filler is one of titanium dioxide and carbon black, and the particle size is 0.5-2 μm;
[0023] The following are further improvements to the above technical solution:
[0024] Step 1: Preparation of toughening-crystallization nucleation composite
[0025] (1) Preparation of modified nano-silica
[0026] After drying the nano-silicon dioxide at 90-120°C for 8-13 hours, the nano-silicon dioxide is placed in a high-speed dispersion reactor, and then toluene and oleic acid amide propyl dimethylamine are added, and the dispersion rate is controlled at 8000-13000 rpm, and after strong dispersion for 5-10 hours, the dispersion rate is reduced to 1500-3000 rpm, and then the temperature is raised and kept constant at 80-100°C, and an aminosilane coupling agent is added under a condensation reflux state, and the reaction is carried out at a constant temperature for 4-9 hours, and then maleic anhydride is added, and the reaction is continued at a constant temperature for 3-7 hours, and then the temperature is cooled to room temperature, and the material is filtered, and the filtered solid is washed with anhydrous ethanol for 2-3 times, and then dried in a 50-70°C oven for 6-10 hours to obtain modified nano-silicon dioxide;
[0027] The particle size of the nano silicon dioxide is 10-100 nm;
[0028] The aminosilane coupling agent is one of γ-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane;
[0029] The mass ratio of the nano silicon dioxide, toluene, oleic acid amide propyl dimethylamine, aminosilane coupling agent and maleic anhydride is 10-50:130-260:1-4:3-10:5-20.
[0030] (2) Preparation of modified nano-hydrotalcite
[0031] After drying the nano hydrotalcite at 100-140°C for 5-11 hours, the nano hydrotalcite is placed in a high-speed dispersion reactor, and then acetone is added. The dispersion rate is controlled at 6000-10000 rpm, and after strong dispersion for 6-12 hours, the dispersion rate is reduced to 1300-2500 rpm, and then the temperature is raised and kept constant at 40-60°C. Under the condensation reflux state, 3-isocyanate propyl trimethoxy silane is added, and the reaction is continued at constant temperature for 5-11 hours. Maleic acid is added, and the reaction is continued at constant temperature for 5-10 hours. Then, the reaction is cooled to room temperature, the material is discharged and filtered, and the filtered solid is washed with anhydrous ethanol for 2-3 times, and then dried in an oven at 60-90°C for 4-9 hours to obtain the modified nano hydrotalcite;
[0032] The particle size of the nano hydrotalcite is 10-100 nm;
[0033] The mass ratio of the nano-hydrotalcite, acetone, 3-isocyanate propyltrimethoxysilane and maleic acid is 20-70:150-290:5-15:15-40.
[0034] (3) Preparation of toughening-crystallization nucleation composite
[0035] A ketone solvent is added to a high-speed dispersion kettle, and then modified nano-silicon dioxide and modified nano-hydrotalcite are added. The dispersion rate is controlled at 9500-13000 rpm, and after strong dispersion for 8-15 hours, the dispersion rate is reduced to 6500-9000 rpm, and ASA high-rubber powder is added at a speed of 1-8 g / min. After the addition is completed, strong dispersion is performed for 4-9 hours, and then the terminal carboxyl hyperbranched polyester is added at a speed of 1-10 g / min. After the addition is completed, the dispersion is continued for 7-13 hours, and then deionized water is added. After continuing to disperse and precipitate for 1-2.5 hours, the material is discharged and filtered, and the filtered solid is washed with deionized water for 2-4 times, and then dried at 70-95° C. for 8-14 hours to obtain a toughening-crystallization nucleation composite agent;
[0036] The ketone solvent is one of acetone and methyl ethyl ketone;
[0037] The ASA high rubber powder is a terpolymer of acrylate-styrene-acrylonitrile copolymerized by emulsion polymerization technology, the inner layer of which is acrylate rubber, and the outer layer is a grafted copolymer of styrene and acrylonitrile, and the melt index is 7-10g / min under the conditions of 220°C and 10kg;
[0038] The carboxyl-terminated hyperbranched polyester has a number average molecular weight of 900-3000 g / mol, a carboxyl number of 6-15 mol / mol, and an acid value of 240-360 mg KOH / g;
[0039] The mass ratio of the ketone solvent, modified nano silicon dioxide, modified nano hydrotalcite, ASA high rubber powder, terminal carboxyl hyperbranched polyester and deionized water is 160-230:10-30:8-20:5-30:10-35:50-100.
[0040] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0041] (1) Melt extrusion
[0042] According to the raw material formula of the strong and tough polyester heat shrinkable film that is not easy to brittle fracture, all the raw materials involved in the formula are dried at 125-155° C. for 2-3.5 hours, and then placed in a dry environment to cool to room temperature. Then, according to the raw material formula of the strong and tough polyester heat shrinkable film that is not easy to brittle fracture in parts by weight, the raw materials are mixed and put into a twin-screw extruder. The heating zones of the twin-screw extruder are heated to 250-275° C. to melt and extrude the mixed raw materials. The melt extruded from the die head is cooled and solidified on the surface of the casting roll to form a casting sheet. By adjusting the number of twin-screw extruders and matching die heads, casting sheets with single-layer, double-layer co-extrusion and three-layer co-extrusion structures are prepared. By adjusting the layer structure and the raw material formula of different layers, this technology can be used for the production of white-black-white polyester heat shrinkable film, low-density white-black-white polyester heat shrinkable film, black-white polyester heat shrinkable film, low-density black-white polyester heat shrinkable film, white polyester heat shrinkable film, low-density white polyester heat shrinkable film, black polyester heat shrinkable film, low-density black polyester heat shrinkable film, transparent polyester heat shrinkable film and other products;
[0043] (2) Stretching
[0044] The stretching comprises stretching the cast sheet using one of a uniaxial stretching process and a biaxial stretching process to obtain a base film;
[0045] The uniaxial stretching process is one of longitudinal stretching and transverse stretching;
[0046] The biaxial stretching process first performs longitudinal stretching and then transverse stretching;
[0047] The longitudinal stretching is performed on a longitudinal stretching machine to form a base film, the stretching temperature is 85-105° C., the ratio is 1-2.5:1, and the tensile strength is 23-85 MPa; the longitudinally stretched base film is heat-set on the surface of a group of cooling rollers, the setting temperature is 70-150° C., and the setting time is 2-5 seconds;
[0048] The transverse stretching is carried out on a transverse stretching machine, the stretching temperature is 85-130°C, the transverse stretching ratio is 2.5-5.5:1, the tensile strength is 193-202MPa, and the stretched base film is heat-set and then cooled, the setting temperature is 55-85°C, and the setting time is 1.5-3 seconds;
[0049] (3) Traction, trimming and winding
[0050] The stretched base film enters the traction station, and the edge device in the traction station trims the edge of the base film with a trimming knife, and then pulls it to the winder to wind the base film to obtain a large roll of strong and tough polyester heat shrinkable film that is not easy to break brittlely.
[0051] Compared with the prior art, the present invention achieves the following beneficial effects:
[0052] 1. The toughening-crystallization nucleation composite agent designed by the present invention is composed of four substances: modified nano-silicon dioxide, modified nano-hydrotalcite, ASA high-rubber powder, and terminal carboxyl hyperbranched polyester. Among them, the modified nano-silicon dioxide mainly plays a role in strengthening and toughening. The modified nano-hydrotalcite is a nano-scale heterogeneous crystallization nucleating agent, which mainly plays a role in promoting the crystallization rate and crystallization refinement of the polyester resin during the hot melt stretching process. The ASA high-rubber powder itself is a toughening agent with particularly good heat resistance, and its heat resistance can match the high temperature of polyester resin processing. In addition, its molecular structure has a large polarity and can be well compatible with the polyester resin matrix, and mainly plays a toughening role. The role played by the terminal carboxyl hyperbranched polyester is relatively multifaceted. The terminal carboxyl hyperbranched polyester and the polyester matrix resin are closely related. The molecular structure of the lipid is most similar, and the compatibility with the polyester matrix resin is the best. Therefore, the terminal carboxyl hyperbranched polyester can effectively promote the compatibility of various raw materials in the raw material formula of the polyester heat shrinkable film, and promote the various raw materials to achieve a uniform mixing effect at the molecular level. In addition, the terminal carboxyl hyperbranched polyester itself has a very low melt viscosity. In the twin-screw extrusion process, the terminal carboxyl hyperbranched polyester can give the polyester formula melt better fluidity, promote the uniform mixing of various materials, and improve the film-forming performance of the formula system during the stretching process. Therefore, the toughening-crystallization nucleation composite agent designed by the present invention is an organically coordinated systematic auxiliary agent system, in which the four substances contained therein influence each other and assist each other to achieve the effect of greatly improving the toughness of the polyester heat shrinkable film;
[0053] 2. The present invention uses oleamide propyl dimethylamine as a dispersant. Under the dispersing effect of oleamide propyl dimethylamine, nano-silica is first dispersed in a toluene solvent, and then an aminosilane coupling agent is added to convert the surface hydroxyl groups of the nano-silica into amino groups, and then the amino groups react with maleic anhydride. After the reaction is completed, the surface of the nano-silica becomes carboxyl groups. The carboxyl-covered nano-silica, the carboxyl-terminated hyperbranched polyester, and the polyester resin in the heat shrink film formula all have a large number of carboxyl groups at the ends of the molecular structures. The similarity in molecular structure promotes the compatibility of the modified nano-silica with the carboxyl-terminated hyperbranched polyester and the polyester resin in the heat shrink film formula. Therefore, the modified nano-silica is easier to be evenly dispersed in the carboxyl-terminated hyperbranched polyester in the pre-dispersion process, and then it is easier to be more evenly dispersed in the polyester resin in the heat shrink film formula, and finally can achieve the best strengthening and toughening effect;
[0054] 3. The present invention uses 3-isocyanate propyl trimethoxy silane and maleic acid to modify the surface of nano hydrotalcite. The surface and interlayer of nano hydrotalcite contain a large number of hydroxyl groups. After 3-isocyanate propyl trimethoxy silane reacts with these hydroxyl groups, the hydroxyl groups on the surface of the nano hydrotalcite are converted into isocyanate groups and a small number of methoxy silane functional groups. Then these two functional groups react with maleic acid again. In this way, the surface and interlayer of the nano hydrotalcite are finally covered with carboxyl functional groups, which is very similar to the surface properties of the above-mentioned modified nano silicon dioxide, and also promotes the nano The hydrotalcite is more evenly dispersed in the polyester resin of the heat shrink film formula. In addition, the nano-hydrotalcite has a layered vertical three-dimensional molecular structure. As a heterogeneous nucleating agent in the polyester crystallization process, this type of molecular structure can induce the formation of polyester crystal nuclei and rapid growth from more three-dimensional dimensions. Therefore, the modified nano-hydrotalcite, relying on its nano-scale dispersion scale and unique three-dimensional molecular structure, can promote the crystallization rate and refinement effect of polyester during the stretching and cooling process, and ultimately improve the mechanical properties of the polyester heat shrink film and the ability to maintain toughness for a long time.
[0055] 4. In the process of preparing the toughening-crystallization nucleation composite agent, the present invention specially designs a pre-dispersion process to ensure that the modified nano-silicon dioxide and the modified nano-hydrotalcite can achieve a nano-scale dispersion effect. By utilizing the convenient condition that both the ASA high-rubber powder and the carboxyl-terminated hyperbranched polyester can be well dissolved in ketone solvents, the modified nano-silicon dioxide and the modified nano-hydrotalcite are first dispersed in the ketone solvent by strong stirring, and then the ASA high-rubber powder and the carboxyl-terminated hyperbranched polyester are slowly added under strong dispersion conditions to make the modified nano-silicon dioxide and the modified nano-hydrotalcite in the form of nano-scale single particles. The inorganic nanopowder and the two polymer molecules can achieve a uniform mixing effect at the molecular scale, which lays a good foundation for the subsequent uniform dispersion in the polyester resin matrix, and also ensures that the four components in the toughening-crystallization nucleation composite agent can ultimately enhance and toughen the polyester heat shrinkable film.
[0056] 5. In the present invention, the crystallization accelerator is formed by mixing trimesic acid amide and 1,2,3-propane tricarbonamide. These two substances have relatively good high temperature resistance. At the same time, because they contain amide groups, they have a large hydrogen bonding effect with the carboxyl hydroxyl group and hydroxyl group at the end of the polyester resin molecular chain. This hydrogen bonding has a certain effect on the orderly arrangement of the molecular chain during the crystallization of the polyester resin, that is, through the hydrogen bonding effect, a certain induction of crystallization effect is achieved. Therefore, these two substances are relatively effective crystallization accelerators, which can induce the rapid crystallization of the polyester resin and promote the refinement of the crystal size, and finally promote the improvement of the mechanical properties of the polyester heat shrinkable film and the long-term retention of toughness;
[0057] 6. The tough polyester heat shrinkable film which is not prone to brittle fracture obtained by the present invention has a thickness of 31.1-51.6 μm, a TD tensile strength of 193-202 MPa, an MD tensile strength of 23-85 MPa, a TD elongation at break of 26-52%, an MD elongation at break of 352-466%, a TD shrinkage of 47-80%, an MD shrinkage of 0-15%, a haze of 4.2-5.0%, a light transmittance of 86.5-87.4%, and after being placed in a normal temperature and humidity environment for 24 months, the elongation at break in the TD and MD directions did not show a significant decrease, and after being placed in a high temperature and high humidity environment for 18 days, the elongation at break in the TD and MD directions did not show a significant decrease either. DETAILED DESCRIPTION
[0058] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0059] Example 1: A method for preparing a tough polyester heat shrinkable film that is not prone to brittle fracture
[0060] Step 1: Preparation of toughening-crystallization nucleation composite
[0061] (1) Preparation of modified nano-silica
[0062] After drying the nano-silica at 100° C. for 11 hours, the nano-silica was placed in a high-speed dispersion reactor, and then toluene and oleic acid amide propyl dimethylamine were added. The dispersion rate was controlled at 12,000 rpm, and after strong dispersion for 8 hours, the dispersion rate was reduced to 1,900 rpm, and then the temperature was raised and kept constant at 95° C., and an aminosilane coupling agent was added under a condensation reflux state. After constant temperature reaction for 6 hours, maleic anhydride was added, and constant temperature reaction was continued for 6 hours, and then the temperature was cooled to room temperature, and the material was filtered. The filtered solid was washed twice with anhydrous ethanol, and then dried in a 65° C. oven for 7 hours to obtain modified nano-silica.
[0063] The particle size of the nano silicon dioxide is 40 nm;
[0064] The aminosilane coupling agent is γ-aminopropyltriethoxysilane;
[0065] The mass ratio of the nano-silica, toluene, oleyl amide propyl dimethylamine, aminosilane coupling agent and maleic anhydride is 30:200:2:7:15.
[0066] (2) Preparation of modified nano-hydrotalcite
[0067] After drying the nano hydrotalcite at 130°C for 6 hours, the nano hydrotalcite was placed in a high-speed dispersion reactor, and acetone was added. The dispersion rate was controlled at 9000 rpm, and after intensive dispersion for 10 hours, the dispersion rate was reduced to 2100 rpm, and the temperature was then raised and kept constant at 55°C. Under the condensation reflux state, 3-isocyanate propyl trimethoxy silane was added, and the reaction was continued at constant temperature for 9 hours. Maleic acid was added, and the reaction was continued at constant temperature for 7 hours. The reaction was cooled to room temperature, the material was filtered, and the filtered solid was washed twice with anhydrous ethanol, and then dried in an oven at 80°C for 7 hours to obtain the modified nano hydrotalcite.
[0068] The particle size of the nano hydrotalcite is 50 nm;
[0069] The mass ratio of the nano-hydrotalcite, acetone, 3-isocyanate propyltrimethoxysilane and maleic acid is 60:250:11:30.
[0070] (3) Preparation of toughening-crystallization nucleation composite
[0071] A ketone solvent is added to a high-speed dispersion kettle, and then modified nano-silicon dioxide and modified nano-hydrotalcite are added. After controlling the dispersion rate at 11000 rpm and dispersing vigorously for 11 hours, the dispersion rate is reduced to 7500 rpm, and ASA high-rubber powder is added at a rate of 5 g / min. After the addition is completed, the powder is dispersed vigorously for 7 hours. Then, the terminal carboxyl hyperbranched polyester is added at a rate of 8 g / min. After the addition is completed, the powder is dispersed for 11 hours, and then deionized water is added. After the dispersion precipitation is continued for 2 hours, the material is filtered, and the filtered solid is washed with deionized water for 3 times, and then dried at 90° C. for 10 hours to obtain a toughening-crystallization nucleation composite agent;
[0072] The ketone solvent is acetone;
[0073] The ASA high rubber powder is a terpolymer of acrylate-styrene-acrylonitrile copolymerized by emulsion polymerization technology, the inner layer of which is acrylate rubber, and the outer layer is a grafted copolymer of styrene and acrylonitrile, and the melt index is 9g / min under the conditions of 220°C and 10kg;
[0074] The carboxyl-terminated hyperbranched polyester has a number average molecular weight of 2000 g / mol, a carboxyl number of 9 mol / mol, and an acid value of 280 mg KOH / g;
[0075] The mass ratio of the ketone solvent, modified nano silicon dioxide, modified nano hydrotalcite, ASA high rubber powder, terminal carboxyl hyperbranched polyester and deionized water is 190:19:15:20:18:70.
[0076] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0077] The raw material formula of the tough polyester heat shrinkable film that is not prone to brittle fracture is, in parts by weight:
[0078] 80 parts of pure polyethylene terephthalate,
[0079] 25 parts of glycol-modified polyethylene terephthalate,
[0080] 9 parts of polybutylene terephthalate,
[0081] 7 parts of toughening-crystallization nucleating compound agent,
[0082] 2 parts of crystallization accelerator,
[0083] 1 part of opening lubricant;
[0084] The pure polyethylene terephthalate has a glass transition temperature of 83°C, a melting temperature of 265°C, an intrinsic viscosity of 0.6 dl / g, and a number average molecular weight of 18000 g / mol;
[0085] The diol-modified polyethylene terephthalate is polyethylene terephthalate co-modified with neopentyl glycol and diethylene glycol, wherein the molar percentage of neopentyl glycol is 32% and the molar percentage of diethylene glycol is 8%;
[0086] The diol-modified polyethylene terephthalate has a glass transition temperature of 78° C., a melting temperature of 245° C., an intrinsic viscosity of 0.8 dl / g, and a number average molecular weight of 19000 g / mol;
[0087] The polybutylene terephthalate has a glass transition temperature of 47° C., a melting temperature of 235° C., an intrinsic viscosity of 0.8 dl / g, and a number average molecular weight of 38,000 g / mol;
[0088] The crystallization accelerator is a mixture of trimesic acid amide and 1,2,3-propane tricarboxamide, and the mass ratio of the two is 7:13;
[0089] The opening lubricant is silicon dioxide with a particle size of 2 μm;
[0090] (1) Melt extrusion
[0091] According to the raw material formula of the strong and tough polyester heat shrinkable film which is not easy to be brittle fractured, all the raw materials involved in the formula are dried at 140° C. for 3 hours, and then placed in a dry environment to cool to room temperature, and then according to the raw material formula of the strong and tough polyester heat shrinkable film which is not easy to be brittle fractured in parts by weight, the raw materials are mixed and put into a twin-screw extruder, and the heating zones of the twin-screw extruder are heated to 260° C., so that the mixed raw materials are melted and extruded, and the melt extruded from the die head is cooled and solidified on the surface of the casting roller to form a casting sheet;
[0092] (2) Stretching
[0093] The stretching comprises stretching the cast sheet using a biaxial stretching process to obtain a base film;
[0094] The biaxial stretching process first performs longitudinal stretching and then transverse stretching;
[0095] The longitudinal stretching is performed on a longitudinal stretching machine to form a base film, the stretching temperature is 90°C, the ratio is 1.5:1, and the tensile strength is 60MPa; the longitudinally stretched base film is heat-set on the surface of a group of cooling rollers, the setting temperature is 110°C, and the setting time is 4 seconds;
[0096] The transverse stretching is carried out on a transverse stretching machine, the stretching temperature is 110°C, the transverse stretching ratio is 4:1, the tensile strength is 200MPa, and the stretched base film is heat-set and then cooled, the setting temperature is 75°C, and the setting time is 2 seconds;
[0097] (3) Traction, trimming and winding:
[0098] The stretched base film enters the traction station, and the edge device in the traction station trims the edge of the base film with a trimming knife, and then pulls it to the winder to wind the base film to obtain a large roll of strong and tough polyester heat shrinkable film that is not easy to break brittlely.
[0099] Example 2: A method for preparing a tough polyester heat shrinkable film that is not prone to brittle fracture
[0100] Step 1: Preparation of toughening-crystallization nucleation composite
[0101] (1) Preparation of modified nano-silica
[0102] After drying the nano-silica at 90°C for 8 hours, the nano-silica was placed in a high-speed dispersion reactor, and then toluene and oleic acid amide propyl dimethylamine were added. The dispersion rate was controlled at 8000 rpm, and after strong dispersion for 5 hours, the dispersion rate was reduced to 1500 rpm, and then the temperature was raised and kept constant at 80°C, and the aminosilane coupling agent was added under the condensation reflux state. After the constant temperature reaction for 4 hours, maleic anhydride was added, and the constant temperature reaction was continued for 3 hours, and then the temperature was cooled to room temperature, and the material was filtered. The filtered solid was washed with anhydrous ethanol twice, and then dried in a 50°C oven for 6 hours to obtain modified nano-silica.
[0103] The particle size of the nano silicon dioxide is 10 nm;
[0104] The aminosilane coupling agent is 3-aminopropyltrimethoxysilane;
[0105] The mass ratio of the nano silicon dioxide, toluene, oleyl amide propyl dimethylamine, aminosilane coupling agent and maleic anhydride is 10:130:1:3:5.
[0106] (2) Preparation of modified nano-hydrotalcite
[0107] The nano hydrotalcite was dried at 100°C for 5 hours, and then placed in a high-speed dispersion reactor. Acetone was then added, and the dispersion rate was controlled at 6000 rpm. After intensive dispersion for 6 hours, the dispersion rate was reduced to 1300 rpm, and then the temperature was raised and kept constant at 40°C. Under the condensation reflux state, 3-isocyanate propyl trimethoxy silane was added, and the reaction was continued at constant temperature for 5 hours. Maleic acid was added, and the reaction was continued at constant temperature for 5 hours. Then, the reaction was cooled to room temperature, the material was filtered, and the filtered solid was washed twice with anhydrous ethanol, and then dried in a 60°C oven for 4 hours to obtain the modified nano hydrotalcite.
[0108] The particle size of the nano hydrotalcite is 10 nm;
[0109] The mass ratio of the nano-hydrotalcite, acetone, 3-isocyanate propyltrimethoxysilane and maleic acid is 20:150:5:15.
[0110] (3) Preparation of toughening-crystallization nucleation composite
[0111] A ketone solvent is added to a high-speed dispersion kettle, and then modified nano-silicon dioxide and modified nano-hydrotalcite are added. After controlling the dispersion rate at 9500 rpm and dispersing vigorously for 8 hours, the dispersion rate is reduced to 6500 rpm, and ASA high-rubber powder is added at a rate of 1 g / min. After the addition is completed, it is dispersed vigorously for 4 hours. Then, the terminal carboxyl hyperbranched polyester is added at a rate of 1 g / min. After the addition is completed, it is dispersed for 7 hours, and then deionized water is added. After continuing to disperse and precipitate for 1 hour, the material is filtered, and the filtered solid is washed with deionized water twice, and then dried at 70°C for 8 hours to obtain a toughening-crystallization nucleation composite agent;
[0112] The ketone solvent is methyl ethyl ketone;
[0113] The ASA high rubber powder is a terpolymer of acrylate-styrene-acrylonitrile copolymerized by emulsion polymerization technology, the inner layer of which is acrylate rubber, and the outer layer is a grafted copolymer of styrene and acrylonitrile, and the melt index is 7g / min under the conditions of 220°C and 10kg;
[0114] The carboxyl-terminated hyperbranched polyester has a number average molecular weight of 900 g / mol, a carboxyl number of 6 mol / mol, and an acid value of 240 mg KOH / g;
[0115] The mass ratio of the ketone solvent, modified nano silicon dioxide, modified nano hydrotalcite, ASA high rubber powder, terminal carboxyl hyperbranched polyester and deionized water is 160:10:8:5:10:50.
[0116] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0117] The raw material formula of the tough polyester heat shrinkable film that is not prone to brittle fracture is, in parts by weight:
[0118] 40 parts of pure polyethylene terephthalate,
[0119] 15 parts of glycol-modified polyethylene terephthalate,
[0120] 4 parts of polybutylene terephthalate,
[0121] 3 parts of toughening-crystallization nucleating compound agent,
[0122] 1 part of crystallization accelerator,
[0123] 0.5 parts of opening lubricant;
[0124] The pure polyethylene terephthalate has a glass transition temperature of 75° C., a melting temperature of 250° C., an intrinsic viscosity of 0.5 dl / g, and a number average molecular weight of 15000 g / mol;
[0125] The glycol-modified polyethylene terephthalate is polyethylene terephthalate co-modified with neopentyl glycol and diethylene glycol, wherein the molar percentage of neopentyl glycol is 25% and the molar percentage of diethylene glycol is 5%;
[0126] The diol-modified polyethylene terephthalate has a glass transition temperature of 70° C., a melting temperature of 220° C., an intrinsic viscosity of 0.4 dl / g, and a number average molecular weight of 17000 g / mol;
[0127] The polybutylene terephthalate has a glass transition temperature of 43°C, a melting temperature of 220°C, an intrinsic viscosity of 0.6 dl / g, and a number average molecular weight of 35000 g / mol;
[0128] The crystallization accelerator is a mixture of trimesic acid amide and 1,2,3-propane tricarboxamide, and the mass ratio of the two is 1:13;
[0129] The opening lubricant is silicon dioxide with a particle size of 1 μm;
[0130] (1) Melt extrusion
[0131] According to the raw material formula of the strong and tough polyester heat shrinkable film which is not easy to be brittle fractured, all the raw materials involved in the formula are dried at 125° C. for 2 hours, and then placed in a dry environment to cool to room temperature, and then according to the raw material formula of the strong and tough polyester heat shrinkable film which is not easy to be brittle fractured in parts by weight, the raw materials are mixed and put into a twin-screw extruder, and the heating zones of the twin-screw extruder are heated to 250° C., so that the mixed raw materials are melted and extruded, and the melt extruded from the die head is cooled and solidified on the surface of the casting roller to form a casting sheet;
[0132] (2) Stretching
[0133] The stretching comprises stretching the cast sheet using a biaxial stretching process to obtain a base film;
[0134] The biaxial stretching process first performs longitudinal stretching and then transverse stretching;
[0135] The longitudinal stretching is performed on a longitudinal stretching machine to form a base film, the stretching temperature is 85°C, the ratio is 1:1, and the tensile strength is 23MPa; the longitudinally stretched base film is heat-set on the surface of a group of cooling rollers, the setting temperature is 70°C, and the setting time is 2 seconds;
[0136] The transverse stretching is carried out on a transverse stretching machine at a stretching temperature of 85°C, a transverse stretching ratio of 2.5:1, and a tensile strength of 193 MPa. The stretched base film is heat-set and then cooled at a setting temperature of 55°C and a setting time of 1.5 seconds.
[0137] (3) Traction, trimming and winding:
[0138] The stretched base film enters the traction station, and the edge device in the traction station trims the edge of the base film with a trimming knife, and then pulls it to the winder to wind the base film to obtain a large roll of strong and tough polyester heat shrinkable film that is not easy to break brittlely.
[0139] Example 3: A method for preparing a tough polyester heat shrinkable film that is not prone to brittle fracture
[0140] Step 1: Preparation of toughening-crystallization nucleation composite
[0141] (1) Preparation of modified nano-silica
[0142] After drying the nano-silica at 120° C. for 13 hours, the nano-silica was placed in a high-speed dispersion reactor, and then toluene and oleic acid amide propyl dimethylamine were added. After controlling the dispersion rate at 13,000 rpm and dispersing vigorously for 10 hours, the dispersion rate was reduced to 3,000 rpm, and then the temperature was raised and kept constant at 100° C., and an aminosilane coupling agent was added under a condensation reflux state. After constant temperature reaction for 9 hours, maleic anhydride was added, and constant temperature reaction was continued for 7 hours, and then the temperature was cooled to room temperature, and the material was filtered. The filtered solid was washed with anhydrous ethanol for 3 times, and then dried in a 70° C. oven for 10 hours to obtain modified nano-silica.
[0143] The particle size of the nano silicon dioxide is 100 nm;
[0144] The aminosilane coupling agent is γ-aminopropyltriethoxysilane;
[0145] The mass ratio of the nano-silica, toluene, oleyl amide propyl dimethylamine, aminosilane coupling agent and maleic anhydride is 50:260:4:10:20.
[0146] (2) Preparation of modified nano-hydrotalcite
[0147] After drying the nano hydrotalcite at 140°C for 11 hours, the nano hydrotalcite was placed in a high-speed dispersion reactor, and then acetone was added. The dispersion rate was controlled at 10,000 rpm, and after intensive dispersion for 12 hours, the dispersion rate was reduced to 2,500 rpm, and then the temperature was raised and kept constant at 60°C. Under the condensation reflux state, 3-isocyanate propyl trimethoxy silane was added, and the reaction was continued at constant temperature for 11 hours. Maleic acid was added, and the reaction was continued at constant temperature for 10 hours. The reaction was cooled to room temperature, the material was filtered, and the filtered solid was washed with anhydrous ethanol for 3 times, and then dried in a 90°C oven for 9 hours to obtain the modified nano hydrotalcite;
[0148] The particle size of the nano hydrotalcite is 100 nm;
[0149] The mass ratio of the nano-hydrotalcite, acetone, 3-isocyanate propyltrimethoxysilane and maleic acid is 70:290:15:40.
[0150] (3) Preparation of toughening-crystallization nucleation composite
[0151] A ketone solvent is added to a high-speed dispersion kettle, and then modified nano-silica and modified nano-hydrotalcite are added. After controlling the dispersion rate at 13,000 rpm and dispersing vigorously for 15 hours, the dispersion rate is reduced to 9,000 rpm, and ASA high-rubber powder is added at a rate of 8 g / min. After the addition is completed, it is dispersed vigorously for 9 hours. Then, the terminal carboxyl hyperbranched polyester is added at a rate of 10 g / min. After the addition is completed, it is dispersed for 13 hours, and then deionized water is added. After continuing to disperse and precipitate for 2.5 hours, the material is filtered, and the filtered solid is washed with deionized water for 4 times, and then dried at 95° C. for 14 hours to obtain a toughening-crystallization nucleation composite agent;
[0152] The ketone solvent is acetone;
[0153] The ASA high rubber powder is a terpolymer of acrylate-styrene-acrylonitrile copolymerized by emulsion polymerization technology, the inner layer of which is acrylate rubber, and the outer layer is a grafted copolymer of styrene and acrylonitrile, and the melt index is 10g / min under the conditions of 220°C and 10kg;
[0154] The carboxyl-terminated hyperbranched polyester has a number average molecular weight of 3000 g / mol, a carboxyl number of 15 mol / mol, and an acid value of 360 mg KOH / g;
[0155] The mass ratio of the ketone solvent, modified nano-silica, modified nano-hydrotalcite, ASA high-rubber powder, carboxyl-terminated hyperbranched polyester, and deionized water is 230:30:20:30:35:100.
[0156] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0157] The raw material formula of the tough polyester heat shrinkable film that is not prone to brittle fracture is, in parts by weight:
[0158] 100 parts of pure polyethylene terephthalate,
[0159] 50 parts of glycol-modified polyethylene terephthalate,
[0160] 15 parts of polybutylene terephthalate,
[0161] 13 parts of toughening-crystallization nucleation compound agent,
[0162] 3.5 parts of crystallization accelerator,
[0163] 2 parts of opening lubricant;
[0164] The pure polyethylene terephthalate has a glass transition temperature of 85°C, a melting temperature of 270°C, an intrinsic viscosity of 0.7 dl / g, and a number average molecular weight of 20,000 g / mol;
[0165] The diol-modified polyethylene terephthalate is polyethylene terephthalate co-modified with neopentyl glycol and diethylene glycol, wherein the molar percentage of neopentyl glycol is 35% and the molar percentage of diethylene glycol is 15%;
[0166] The diol-modified polyethylene terephthalate has a glass transition temperature of 83° C., a melting temperature of 260° C., an intrinsic viscosity of 1.0 dl / g, and a number average molecular weight of 21000 g / mol;
[0167] The polybutylene terephthalate has a glass transition temperature of 50° C., a melting temperature of 240° C., an intrinsic viscosity of 1.0 dl / g, and a number average molecular weight of 40,000 g / mol;
[0168] The crystallization accelerator is a mixture of trimesic acid amide and 1,2,3-propane tricarboxamide, and the mass ratio of the two is 10:13;
[0169] The opening lubricant is silicon dioxide with a particle size of 5 μm;
[0170] (1) Melt extrusion
[0171] According to the raw material formula of the strong and tough polyester heat shrinkable film which is not easy to be brittle fractured, all the raw materials involved in the formula are dried at 155° C. for 3.5 hours, and then placed in a dry environment to cool to room temperature, and then according to the raw material formula of the strong and tough polyester heat shrinkable film which is not easy to be brittle fractured in parts by weight, the raw materials are mixed and put into a twin-screw extruder, and the heating zones of the twin-screw extruder are heated to 275° C., so that the mixed raw materials are melted and extruded, and the melt extruded from the die head is cooled and solidified on the surface of the casting roller to form a casting sheet;
[0172] (2) Stretching
[0173] The stretching comprises stretching the cast sheet using a biaxial stretching process to obtain a base film;
[0174] The biaxial stretching process first performs longitudinal stretching and then transverse stretching;
[0175] The longitudinal stretching is performed on a longitudinal stretching machine to form a base film, the stretching temperature is 105°C, the ratio is 2.5:1, and the tensile strength is 85MPa; the longitudinally stretched base film is heat-set on the surface of a group of cooling rollers, the setting temperature is 150°C, and the setting time is 5 seconds;
[0176] The transverse stretching is carried out on a transverse stretching machine, the stretching temperature is 130°C, the transverse stretching ratio is 5.5:1, the tensile strength is 202MPa, and the stretched base film is heat-set and then cooled, the setting temperature is 85°C, and the setting time is 3 seconds;
[0177] (3) Traction, trimming and winding:
[0178] The stretched base film enters the traction station, and the edge device in the traction station trims the edge of the base film with a trimming knife, and then pulls it to the winder to wind the base film to obtain a large roll of strong and tough polyester heat shrinkable film that is not easy to break brittlely.
[0179] Example 4: A method for preparing a tough polyester heat shrinkable film that is not prone to brittle fracture
[0180] The operation of step 1 is the same as that of embodiment 1;
[0181] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0182] The raw material formula of the tough polyester heat shrinkable film that is not prone to brittle fracture is, in parts by weight:
[0183] 100 parts of pure polyethylene terephthalate,
[0184] 50 parts of glycol-modified polyethylene terephthalate,
[0185] 15 parts of polybutylene terephthalate,
[0186] 13 parts of toughening-crystallization nucleation compound agent,
[0187] 3.5 parts of crystallization accelerator,
[0188] 2 parts of opening lubricant,
[0189] 8 parts of filler;
[0190] The filler is titanium dioxide with a particle size of 0.5 μm;
[0191] The other operations are the same as those in Example 1.
[0192] Example 5: A method for preparing a tough polyester heat shrinkable film that is not prone to brittle fracture
[0193] The operation of step 1 is the same as that of embodiment 1;
[0194] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0195] The raw material formula of the tough polyester heat shrinkable film that is not prone to brittle fracture is, in parts by weight:
[0196] 100 parts of pure polyethylene terephthalate,
[0197] 50 parts of glycol-modified polyethylene terephthalate,
[0198] 15 parts of polybutylene terephthalate,
[0199] 13 parts of toughening-crystallization nucleation compound agent,
[0200] 3.5 parts of crystallization accelerator,
[0201] 2 parts of opening lubricant,
[0202] 15 parts of filler;
[0203] The filler is carbon black with a particle size of 2 μm;
[0204] The other operations are the same as those in Example 1.
[0205] Comparative Example 1: Based on Example 1, in step 1, in the preparation of the toughening-crystallization nucleation composite, (1) the preparation of modified nano-silica is not performed, and in the step (3) of preparing the toughening-crystallization nucleation composite, 19 parts of modified nano-silica are replaced by 19 parts of ketone solvent in an equal amount. The specific operation is as follows:
[0206] Step 1: Preparation of toughening-crystallization nucleation composite
[0207] (1) Preparation of modified nano-silica is not performed;
[0208] (2) Preparation of modified nano-hydrotalcite, the operation is the same as Example 1;
[0209] (3) Preparation of toughening-crystallization nucleation composite
[0210] 19 parts of modified nano-silicon dioxide were replaced by 19 parts of ketone solvent, and other operations were the same as in Example 1;
[0211] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0212] The operation is the same as in Example 1.
[0213] Comparative Example 2: Based on Example 1, in step 1, in the preparation of the toughening-crystallization nucleating composite agent, (2) the preparation of the modified nano-hydrotalcite was not performed, and in the step (3) of preparing the toughening-crystallization nucleating composite agent, 15 parts of the modified nano-hydrotalcite were replaced by 15 parts of a ketone solvent in an equal amount. The specific operation was as follows:
[0214] Step 1: Preparation of toughening-crystallization nucleation composite
[0215] (1) Prepare modified nano-silicon dioxide by the same operation as in Example 1;
[0216] (2) Preparation of modified nano-hydrotalcite was not performed;
[0217] (3) Preparation of toughening-crystallization nucleation composite
[0218] 15 parts of modified nano-hydrotalcite were replaced by 15 parts of ketone solvent, and other operations were the same as in Example 1;
[0219] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0220] The operation is the same as in Example 1.
[0221] Comparative Example 3: Based on Example 1, in step 1, preparation of toughening-crystallization nucleation composite agent, (3) in the step of preparing toughening-crystallization nucleation composite agent, no ASA high-rubber powder is added, and 20 parts of ASA high-rubber powder are replaced by 20 parts of ketone solvent in equal amounts. The specific operation is as follows:
[0222] Step 1: Preparation of toughening-crystallization nucleation composite
[0223] (1) Prepare modified nano-silicon dioxide by the same operation as in Example 1;
[0224] (2) Preparation of modified nano-hydrotalcite, the operation is the same as Example 1;
[0225] (3) Preparation of toughening-crystallization nucleation composite
[0226] The 20 parts of ASA high-rubber powder were replaced by 20 parts of ketone solvent, and the other operations were the same as in Example 1;
[0227] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0228] The operation is the same as in Example 1.
[0229] Comparative Example 4: Based on Example 1, in step 1, preparing the toughening-crystallization nucleating composite, (3) in the step of preparing the toughening-crystallization nucleating composite, no carboxyl-terminated hyperbranched polyester is added, and 18 parts of carboxyl-terminated hyperbranched polyester are replaced by 18 parts of ketone solvent in equal amounts. The specific operation is as follows:
[0230] Step 1: Preparation of toughening-crystallization nucleation composite
[0231] (1) Prepare modified nano-silicon dioxide by the same operation as in Example 1;
[0232] (2) Preparation of modified nano-hydrotalcite, the operation is the same as Example 1;
[0233] (3) Preparation of toughening-crystallization nucleation composite
[0234] 18 parts of carboxyl-terminated hyperbranched polyester were replaced by 18 parts of ketone solvent, and the other operations were the same as in Example 1;
[0235] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0236] The operation is the same as in Example 1.
[0237] Comparative Example 5: Based on Example 1, in step 2, in the preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture, no crystallization accelerator is added, and 2 parts of the crystallization accelerator are replaced by 2 parts of pure polyethylene terephthalate in equal amounts. The specific operation is as follows:
[0238] Step 1: Preparation of toughening-crystallization nucleation composite
[0239] The operation is the same as in Example 1;
[0240] Step 2: Preparation of a tough polyester heat shrinkable film that is not prone to brittle fracture
[0241] The 2 parts of crystallization accelerator were replaced by 2 parts of pure polyethylene terephthalate in equal amounts, and the other operations were the same as in Example 1.
[0242] Performance Test:
[0243] The tough polyester heat shrinkable films obtained in Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2, 3, 4, 5 and which are not prone to brittle fracture, were tested for the following performance indicators:
[0244] 1. Thickness: According to ASTM D374, the film thickness value was measured using a thickness tester (Millimar1240) produced by Mahr Company of Germany;
[0245] 2. Mechanical strength: tensile strength and elongation at break shall comply with ASTM D882 standard;
[0246] 3. Shrinkage rate: Tested according to ASTM D1204 standard;
[0247] 4. Light transmittance: According to ASTM D1003, tested with Nippon Denshoku NDH-5000;
[0248] 5. Haze value: According to ASTM D1003, the haze value of the film was measured using a haze tester (BS 2782) produced by Diffusion System, UK;
[0249] 6. Long-term toughness retention in normal temperature and humidity environment: In an environment with a temperature of 25°C and a relative humidity of 55%, test the elongation at break after 1, 6, 12, 18, and 24 months, and record the changes in the elongation at break;
[0250] 7. Long-term toughness retention in high temperature and high humidity environment: In an environment with a temperature of 40°C and a relative humidity of 80%, test the elongation at break after 1, 3, 6, 12, and 18 days, and record the changes in the elongation at break;
[0251] Test data are shown in Table 1, Table 2, and Table 3:
[0252] Table 1 Conventional performance test
[0253]
[0254] From the data in Table 1, it can be seen that the tensile strength in the TD direction of Examples 1-5 is about 200 MPa, the tensile strength in the MD direction is above 20 MPa, the elongation at break in the TD direction exceeds 26%, the elongation at break in the MD direction is above 350%, the heat shrinkage in the TD direction is above 47%, and the heat shrinkage in the MD direction is between 0 and 15%. The haze of Examples 1-3 is relatively low, and the light transmittance is relatively good, which shows that the polyester heat shrinkable film obtained by the present invention has good heat shrinkage performance, and also has the advantages of high strength and high toughness in terms of mechanical properties. At the same time, the haze and light transmittance of the transparent film fully meet the requirements of the plastic packaging industry. The requirements are met; the modified nano-silica is not added to the toughening-crystallization nucleation composite agent of Comparative Example 1, the tensile strength and elongation at break of Comparative Example 1 are greatly reduced, the shrinkage in the TD direction is also significantly reduced, and the haze and light transmittance are slightly improved, which shows that the modified nano-silica plays a very significant role in strengthening and toughening, and the dispersion uniformity is relatively good, and the haze and light transmittance are basically not affected; the modified nano-hydrotalcite is not added to the toughening-crystallization nucleation composite agent of Comparative Example 2, and the situation of Comparative Example 2 is similar to that of Comparative Example 1, the tensile strength and elongation at break are significantly reduced, but the reduction is less than that of Comparative Example 1, and the shrinkage in the TD direction is slightly improved. The shrinkage rate is also reduced to a certain extent, and the haze and transmittance are similar to those of Comparative Example 1, with a slight improvement, which shows that the modified nano-hydrotalcite can also play a relatively important role in strengthening and toughening. Like the modified nano-silicon dioxide, it can also be well dispersed in the polyester resin matrix under the pre-dispersion process designed by the present invention, and thus has no significant effect on the haze and transmittance; the ASA high rubber powder is not added to the toughening-crystallization nucleation composite agent of Comparative Example 3, and the tensile strength of Comparative Example 3 has a relatively obvious slight decrease, the elongation at break in the MD direction decreases significantly, the shrinkage rate in the TD direction also decreases significantly, and the haze and transmittance are basically unchanged, which means that It is clear that the main function of ASA high-rubber powder is to improve the toughness of polyester heat shrinkable film, and after the pre-dispersion process, the compatibility of ASA high-rubber powder with polyester matrix resin is relatively good, and there is no obvious effect on the haze and transmittance; in the toughening-crystallization nucleation composite agent of comparative example 4, no carboxyl-terminated hyperbranched polyester is added, and the tensile strength, elongation at break and shrinkage of comparative example 4 are sharply reduced, and the haze and transmittance are also significantly deteriorated, which shows that the carboxyl-terminated hyperbranched polyester plays a key role in improving the mechanical properties of polyester heat shrinkable film, promoting the uniformity of dispersion of other powdery materials and promoting the crystallization rate of polyester matrix resin.In the formula of comparative example 5, a strong and tough polyester heat shrinkable film that is not prone to brittle fracture, no crystallization accelerator is added. The tensile strength and elongation at break in the MD direction of comparative example 5 are significantly reduced, the shrinkage is also reduced to a certain extent, and the haze and light transmittance do not change much, which shows that the crystallization accelerator plays a vital role in improving the mechanical properties of the polyester resin matrix, and can be combined with other reinforcing fillers in the formula system to jointly promote the improvement of the strength and toughness of the polyester heat shrinkable film. ;
[0255] Table 2 Long-term toughness retention in normal temperature and humidity environment
[0256]
[0257] From the data in Table 1, it can be seen that during the long-term placement in a normal temperature and humidity environment, the elongation at break in the MD and TD directions of Examples 1-5 has been slowly decreasing by a small margin from 1 month to 24 months, and there has been no drastic decline. However, at the 12-month time point, the elongation at break of Comparative Examples 1-5 began to decrease significantly. After 18 and 24 months of placement, the elongation at break dropped to a very low state. It can be seen that the toughening-crystallization nucleation composite agent designed by the present invention and the added crystallization accelerator can play a role in maintaining the good toughness of the polyester heat shrinkable film for a long time and preventing it from brittle fracture.
[0258] Table 3 Toughness retention in high temperature and high humidity environment for a long time
[0259]
[0260] From the data in Table 3, it can be seen that during the long-term placement in a high-temperature and high-humidity environment, the elongation at break of Examples 1-5 in the MD and TD directions has been accompanied by a slight decrease from 1 day to 18 days, and no inflection point of a sharp decrease has appeared, which shows that the polyester heat shrinkable film obtained by the present invention can resist the damage to toughness caused by the harsh environment in a high-temperature and high-humidity environment and can eliminate the problem of brittle fracture; for Comparative Examples 1-5, at the time nodes of 1 day and 3 days of placement, the rate of decrease of the elongation at break is much larger than that of the five embodiments. Starting from the 6th day, the rate of decrease of the elongation at break of Comparative Examples 1-5 is greatly accelerated, showing a sharp downward trend. By the 18th day, for Comparative Examples 1-5, the elongation at break in the MD direction is mostly reduced to below 100%, and the elongation at break in the TD direction is reduced to below 2%. It can be seen that after 18 days, the brittleness of Comparative Examples 1-5 is very obvious, and the problem of brittle fracture is very likely to occur.
[0261] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A tough polyester heat shrinkable film that is not prone to brittle fracture, characterized in that: The raw material formula of the tough polyester heat shrinkable film that is not prone to brittle fracture is, in parts by weight: 40-100 parts of polyethylene terephthalate, 15-50 parts of glycol-modified polyethylene terephthalate, 4-15 parts of polybutylene terephthalate, Toughening-crystallization nucleation compound 3~13 parts, 1~3.5 parts of crystallization accelerator, 0.5~2 parts of opening lubricant, Filler 0~15 parts; The polyethylene terephthalate has a glass transition temperature of 75-85° C., a melting temperature of 250-270° C., an intrinsic viscosity of 0.5-0.7 dl / g, and a number average molecular weight of 15000-20000 g / mol; The diol-modified polyethylene terephthalate is polyethylene terephthalate co-modified with neopentyl glycol and diethylene glycol, wherein the molar percentage of neopentyl glycol is 25-35%, and the molar percentage of diethylene glycol is 5-15%; The diol-modified polyethylene terephthalate has a glass transition temperature of 70-83° C., a melting temperature of 220-260° C., an intrinsic viscosity of 0.4-1.0 dl / g, and a number average molecular weight of 17000-21000 g / mol; The polybutylene terephthalate has a glass transition temperature of 43-50° C., a melting temperature of 220-240° C., an intrinsic viscosity of 0.6-1.0 dl / g, and a number average molecular weight of 35000-40000 g / mol; The crystallization accelerator is a mixture of trimesic acid amide and 1,2,3-propane tricarboxamide, and the mass ratio of the two is 1-10:13; The opening lubricant is silicon dioxide with a particle size of 1 to 5 μm; The filler is one of titanium dioxide and carbon black, and the particle size is 0.5-2 μm; The toughening-crystallization nucleation composite agent, the preparation method of which comprises three steps of preparing modified nano-silicon dioxide, preparing modified nano-hydrotalcite, and preparing the toughening-crystallization nucleation composite agent; The modified nano-silica is prepared by drying the nano-silica at 90-120° C. for 8-13 hours, placing the nano-silica in a high-speed dispersion reactor, then adding toluene and oleamidopropyl dimethylamine, controlling the dispersion rate at 8000-13000 rpm, and dispersing vigorously for 5-10 hours, then reducing the dispersion rate to 1500-3000 rpm, then raising the temperature and keeping the temperature constant at 80-100° C., adding an aminosilane coupling agent while maintaining the temperature under condensation reflux, and reacting at a constant temperature for 4-9 hours, then adding maleic anhydride, continuing the temperature reaction for 3-7 hours, cooling to room temperature, filtering the discharged material, washing the filtered solid with anhydrous ethanol for 2-3 times, and drying it in an oven at 50-70° C. for 6-10 hours to obtain the modified nano-silica; The particle size of the nano silicon dioxide is 10-100 nm; The aminosilane coupling agent is one of γ-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; The modified nano hydrotalcite is prepared by drying the nano hydrotalcite at 100-140°C for 5-11 hours, placing the nano hydrotalcite in a high-speed dispersion reactor, adding acetone, controlling the dispersion rate at 6000-10000 rpm, dispersing vigorously for 6-12 hours, reducing the dispersion rate to 1300-2500 rpm, then heating and maintaining the temperature at 40-60°C, adding 3-isocyanate propyl trimethoxy silane under condensation reflux, reacting at a constant temperature for 5-11 hours, adding maleic acid, continuing the constant temperature reaction for 5-10 hours, cooling to room temperature, filtering the discharged material, washing the filtered solid with anhydrous ethanol for 2-3 times, and drying it in an oven at 60-90°C for 4-9 hours to obtain the modified nano hydrotalcite; The particle size of the nano hydrotalcite is 10-100 nm; The toughening-crystallization nucleation composite agent is prepared by adding a ketone solvent to a high-speed dispersion kettle, then adding modified nano-silicon dioxide and modified nano-hydrotalcite, controlling the dispersion rate at 9500-13000 rpm, and vigorously dispersing for 8-15 hours, then reducing the dispersion rate to 6500-9000 rpm, adding ASA high-rubber powder at a rate of 1-8 g / min, and vigorously dispersing for 4-9 hours after the addition is completed, then adding the terminal carboxyl hyperbranched polyester at a rate of 1-10 g / min, and continuing to disperse for 7-13 hours after the addition is completed, then adding deionized water, continuing to disperse and precipitate for 1-2.5 hours, filtering the discharged material, washing the filtered solid with deionized water for 2-4 times, and drying it at 70-95° C. for 8-14 hours to obtain the toughening-crystallization nucleation composite agent; The ketone solvent is one of acetone and methyl ethyl ketone; The ASA high rubber powder is a terpolymer of acrylate-styrene-acrylonitrile copolymerized by emulsion polymerization technology, the inner layer of which is acrylate rubber, and the outer layer is a grafted copolymer of styrene and acrylonitrile, and the melt index is 7-10g / min under the conditions of 220°C and 10kg; The carboxyl-terminated hyperbranched polyester has a number average molecular weight of 900-3000 g / mol, a carboxyl number of 6-15 mol / mol, and an acid value of 240-360 mg KOH / g.
2. The tough polyester heat shrinkable film that is not prone to brittle fracture according to claim 1, characterized in that: The mass ratio of the nano silicon dioxide, toluene, oleic acid amide propyl dimethylamine, aminosilane coupling agent and maleic anhydride is 10-50:130-260:1-4:3-10:5-20.
3. The tough polyester heat shrinkable film that is not prone to brittle fracture according to claim 1, characterized in that: The mass ratio of the nano-hydrotalcite, acetone, 3-isocyanate propyltrimethoxysilane and maleic acid is 20-70:150-290:5-15:15-40.
4. The tough polyester heat shrinkable film that is not prone to brittle fracture according to claim 1, characterized in that: The mass ratio of the ketone solvent, modified nano silicon dioxide, modified nano hydrotalcite, ASA high rubber powder, terminal carboxyl hyperbranched polyester and deionized water is 160-230:10-30:8-20:5-30:10-35:50-100.
5. The method for preparing a strong and tough polyester heat shrinkable film that is not prone to brittle fracture according to claim 1, characterized in that: The method for preparing the tough polyester heat shrinkable film which is not easy to be brittle fracture comprises three steps of melt extrusion, stretching, traction, trimming and winding; The melt extrusion is carried out according to the raw material formula of the strong and tough polyester heat shrinkable film which is not easy to be brittle fracture, all the raw materials involved in the formula are dried at 125-155° C. for 2-3.5 hours, and then placed in a dry environment to cool to room temperature, and then according to the raw material formula of the strong and tough polyester heat shrinkable film which is not easy to be brittle fracture in parts by weight, the raw materials are mixed and put into a twin-screw extruder, the heating zones of the twin-screw extruder are heated to 250-275° C., the mixed raw materials are melted and extruded, the melt extruded from the die head is cooled and solidified on the surface of the casting roll to form a casting sheet, and the casting sheets with single-layer, double-layer co-extrusion and three-layer co-extrusion structures are prepared by adjusting the number of twin-screw extruders and matching die heads.
6. The method for preparing a strong and tough polyester heat shrinkable film that is not prone to brittle fracture according to claim 5, characterized in that: The stretching comprises stretching the cast sheet using one of a uniaxial stretching process and a biaxial stretching process to obtain a base film; The uniaxial stretching process is one of longitudinal stretching and transverse stretching; The biaxial stretching process first performs longitudinal stretching and then transverse stretching; The longitudinal stretching is performed on a longitudinal stretching machine to form a base film, the stretching temperature is 85-105° C., the ratio is 1-2.5:1, and the tensile strength is 23-85 MPa; the longitudinally stretched base film is heat-set on the surface of a group of cooling rollers, the setting temperature is 70-150° C., and the setting time is 2-5 seconds; The transverse stretching is carried out on a transverse stretching machine, the stretching temperature is 85-130°C, the transverse stretching ratio is 2.5-5.5:1, the tensile strength is 193-202MPa, and the stretched base film is heat-set and then cooled, the setting temperature is 55-85°C, and the setting time is 1.5-3 seconds.
7. The method for preparing a strong and tough polyester heat shrinkable film that is not prone to brittle fracture according to claim 6, characterized in that: The traction, trimming and winding process is carried out, and the stretched base film enters the traction station, and the edge device in the traction station trims the edge of the base film through a trimming knife, and then the base film is pulled to the winding machine to be wound up, so as to obtain a large roll of strong and tough polyester heat shrinkable film that is not easy to be brittle and fractured.
Citation Information
Patent Citations
Flexible polyester thermal contraction membrane and production method thereof
CN105885024A
Quickly crystallized polyester engineering plastic and preparation method thereof
CN101787184A
Low-temperature high-toughness polyester shrink film for thermal shrinkage label as well as preparation method and application of low-temperature high-toughness polyester shrink film
CN115491000A